SUPLEMENTASI RUMPUT LAUT PADA ROTI MANIS BERBASIS TEPUNG KOMPOSIT - . Kartiwan; Zulianatul Hidayah; Bachtaruddin Badewi (Politeknik Pertanian Negeri Kupang, 2008)
The experiment of Seaweed Supplementation on Composite Flour Bases Sweet Bread was conducted at Food Technology Laboratory of Politani Negeri Kupang. The experiment used RCBD with factorial pattern. The factors were Composite flour (0%, 10%, 20%, 30%) and seaweed supplementation (0%, 5%, 10%), and three time replications. The variables observed were volume expansion of dough, porosity, texture, color of crumb, moisture content, total plate count of microorganisms, iodine content and crude fiber content of bread. The data were analyzed using Anova and DMRT test. Seaweed supplementation to bread dough produced the characteristic of bread such as (a) There is no significant on developing of bread, the total of porosity, color of crumb and total plate count of microorganisms, (b) There is significant on texture of bread, the moisture content was increased, iodine content and crude fiber content of bread more higher. Composite flours affected on characteristic of bread: It’s not expansion, the total porosity more higher but the size more narrower, the texture more hard (softness), color of crumb tend darkness, the total microbe colony tend lower, iodine and crude fiber content of bread increased. The best quality sweet bread from this research was the bread made of composite flour 10% and 10% seaweed supplementation.Key words: supplementation, seaweed, composite flours